Microbial Desalination Cells Technology: A Review and a Case Study - Saeed, Henna M (2015)
The microbial desalination cell (MDC) is a newly-developed technology which integrates the microbial fuel cell (MFC) process and electrodialysis for wastewater treatment, water desalination and production of renewable energy. Due to free energy requirements and environmentally friendly technologies, MDC recently received considerable attention for desalination and wastewater treatment. The technology can either be used as a stand-alone process, or can be combined with other desalination processes, such as reverse osmosis (RO) or electrodialysis. Recently, several different modifications of MDCs have been developed including stacked MDCs, biocathode MDCs and recirculation MDCs. This paper provides a general review of the MDC technology. The working principle of the conventional MDC system is discussed, followed by a brief introduction to biofilms and biofilm formation. The different modifications of MDCs and the various advantages and disadvantages associated with each, including the desalination performance and electricity generation are also considered. The issues of scale-up and practical availability of the MDC technology are discussed, followed by a detailed discussion and evaluation of a proposed design for a wastewater treatment plant integrating the MDC technology. A case study of a wastewater treatment plant integrated with MDC technology to simultaneously treat wastewater and desalinate seawater is also considered.